Taurine: A potential mediator for periodontal therapy - Swantika Chaudhry; Bhuvanesh Tandon; Akanksha Gupta; Sugandha Gupta (Wolters Kluwer Medknow Publications, 2018)
Taurine or 2-aminoethanesulfonic has many fundamental biological roles such as conjugation of bile acids, antioxidation, osmoregulation, membrane stabilization, and modulation of calcium signaling. It is essential for cardiovascular function and development and function of the skeletal muscle, the retina, and the central nervous system. Functions of taurine include osmoregulation; membrane stabilization; modulation of calcium levels; and antioxidation, antiapoptotic, anti-inflammatory, and antilipid activities. Taurine was first discovered as a component of ox (Bos taurus, from which its name is derived) bile in 1827; it had taken over a century before insights into its physiological functions were made. The present review throws light on the multifactorial properties of taurine and its potential to be used in periodontal therapy.